2005
DOI: 10.1002/jnr.20666
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco cembranoids protect the function of acute hippocampal slices against NMDA by a mechanism mediated by α4β2 nicotinic receptors

Abstract: Nicotine has been reported to be neuroprotective in experimental and epidemiological studies. In addition to nicotine, tobacco and cigarette smoke contain cembranoids, which are antagonists of neuronal nicotinic receptors (nAChR). Exposure of hippocampal slices to N-methyl-D-aspartate (NMDA) decreases the population spikes (PS). This parameter has been used as a measure of excitotoxicity. Surprisingly, both nicotine and tobacco cembranoids protected against NMDA and this neuroprotection was not blocked by meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 37 publications
6
86
1
Order By: Relevance
“…Considering the hypothesis that hyperstimulation of the cholinergic system over the noradrenergic system results in depressed states (Shytle et al, 2002b;Arias, 2009Arias, , 2010b, the observed inhibitory synergism by Zn 2þ and antidepressants could be of clinical significance. Some cembranoids (e.g., cembra-2,7,11-triene-4,6-diol) inhibit the N-methyl-d-aspartate-induced excitotoxicity in hippocampal neurons by a mechanism mediated by a4b2 AChRs (Ferchmin et al, 2005;reviewed in Ferchmin et al, 2009). In addition to cembra-2,7,11-triene-4,6-diol, eunicin and eupalmerin acetate inhibit the behavioral sensitization to nicotine in rats (Ferchmin et al, 2001;reviewed in Ferchmin et al, 2009).…”
Section: Positive Allosteric Modulatorsmentioning
confidence: 96%
“…Considering the hypothesis that hyperstimulation of the cholinergic system over the noradrenergic system results in depressed states (Shytle et al, 2002b;Arias, 2009Arias, , 2010b, the observed inhibitory synergism by Zn 2þ and antidepressants could be of clinical significance. Some cembranoids (e.g., cembra-2,7,11-triene-4,6-diol) inhibit the N-methyl-d-aspartate-induced excitotoxicity in hippocampal neurons by a mechanism mediated by a4b2 AChRs (Ferchmin et al, 2005;reviewed in Ferchmin et al, 2009). In addition to cembra-2,7,11-triene-4,6-diol, eunicin and eupalmerin acetate inhibit the behavioral sensitization to nicotine in rats (Ferchmin et al, 2001;reviewed in Ferchmin et al, 2009).…”
Section: Positive Allosteric Modulatorsmentioning
confidence: 96%
“…Other tobacco smoke ingredients, such as nitrosamines (i.e. 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N-nitrosonornicotine (NNN) and N-nitrosodiethylamine (DEN)) and cembranoids are also ligands of nAChRs (Zevin and Benowitz, 1999;Ayers et al, 2005;Schuller, 2007;Ferchmin et al, 2005Ferchmin et al, , 2009Cai et al, 2003). Tar consists of polycyclic aromatic hydrocarbons (PAH), metallic ions, several radioactive compounds, and free radicals, as well (Frishman et al, 2006;Swan and Lessov-Schlaggar, 2007;Pryor and Stone, 1993).…”
Section: Pharmacology and Health Consequences Of Smokingmentioning
confidence: 99%
“…Therefore, we took HT22 cells exposed to Aβ 1-42 as the cell injury model to mimic pathogenesis of AD. Since we have found that p r o t e i n k i n a s e C ( P K C ) w a s i n v o l v e d i n t h e electroacupuncture (EA)-induced neuroprotection against brain ischemia through CB1 , some other researchers reported that PKC inhibitor could reverse nicotine-induced neuroprotection against N-methyl-Daspartate (NMDA) in hippocampal slices (Ferchmin et al 2005). However, whether PKC mediates nicotine-induced neuroprotection against Aβ has not been investigated.…”
Section: Introductionmentioning
confidence: 99%